From consensus to conflict in the regional policy mix for broadband deployment: examining the role of informal coordination - Dylan Henderson; Neil Roche (International Telecommunications Society (ITS), 2018)
This paper examines the policy mix for broadband infrastructure deployment, and asks what role is there for coordination agents. While research has begun to examine coordination of policy, analysis has largely focused on organization and structures. This paper seeks to develop this further by examining the informal role that coordination actors play in managing synergies and tensions in the policy mix. The research highlights shared synergies in policy objectives for broadband deployment at multiple levels of governance – EU, UK, regional and local authority. Tensions, however, are found in the deployment process at the regional level, as broadband policy objectives interact with those for highways and planning agendas. In seeking to manage these tensions it highlights three coordination roles – champion, troubleshooter and monitor - and shows how these help to address conflicts and tensions that emerge. While the research suggests such tensions are impossible to fully eliminate, the findings show how the work of these informal actors helps to mediate their effects and support the deployment of broadband. These findings are drawn from an in-depth study of broadband policy in Wales between 2012 and 2017, including interviews with the policy community, analysis of news articles and review of policy documentation.
Keywords: 330